2018
DOI: 10.21608/ejbo.2018.3049.1159
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid triggers adaptation cadmium cytogenetic toxicity in roots of Nigella sativa L.

Abstract: C ADMIUM (Cd) is a toxic heavy-metal pollutant in the environment, it is a nonessential element, which strongly inhibits plant growth and development, and causes plant death even at very low concentrations. Root tip cells of Nigella sativa were separately treated with different concentrations (5, 10, 25 and 50ppm) of cadmium for 3, 6, 12 and 24h and the results were recorded. The results showed that all concentrations of cadmium reduced the mitotic index and caused a disturbance in the frequencies of mitotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…Various cytological irregularities were observed during Cd stress in Nigella sativa while post-treatment of SA resulted in a significant increase in MI% with the reduction in chromosomal aberrations. These results are consistent with our findings that observed increase mitotic index and reduced chromosomal aberrations which confirmed ameliorating property of SA under stress [ 67 ]. It was reported that Cd tends to reduce the mitotic activity of root cells thus decrease plant growth by shortening G2 phases and prophase that facilitates the abnormal spindle formation while SA pretreatment increased the mitotic index.…”
Section: Discussionsupporting
confidence: 94%
“…Various cytological irregularities were observed during Cd stress in Nigella sativa while post-treatment of SA resulted in a significant increase in MI% with the reduction in chromosomal aberrations. These results are consistent with our findings that observed increase mitotic index and reduced chromosomal aberrations which confirmed ameliorating property of SA under stress [ 67 ]. It was reported that Cd tends to reduce the mitotic activity of root cells thus decrease plant growth by shortening G2 phases and prophase that facilitates the abnormal spindle formation while SA pretreatment increased the mitotic index.…”
Section: Discussionsupporting
confidence: 94%
“…For example, SA (10 µM) application to chickpea plants exposed to weak or moderate and strong cadmium (Cd) stress increases, restores and partly restores root length, respectively [231]. In some cases, SA's protective effect is due to it reducing stress factor toxicity [232][233][234] (reviewed in [235]). For example, the application of exogenous SA elevates aluminum (Al)-induced citrate efflux from the roots of Cassia tora, which is associated with an increased tolerance of seedlings to Al [44].…”
Section: Sa Alleviates Changes In Root System Morphology Induced By A...mentioning
confidence: 99%
“…These protective properties of humic or fulvic substances have already been demonstrated by several authors on lettuce against Cd [56] and on radish against Cd, Cu and Zn [57], but not directly on the rate of division in the root apex. The salicylic acid post-treatment of Nigella sativa, exposed to another toxic heavy-metal (cadmium), increases the mitotic index while reducing chromosomal abnormalities [58]. Salicylic acid has a protective action against the genotoxic and toxic effect of heavy metals, as does BHS ® .…”
Section: Protective Effects Of Biostimulants Towards Exposure To Contmentioning
confidence: 99%